KEDUDUKAN SANAD (TRANSMISI HADIS NABI SAW) MENURUT PARA ULAMA KLASIK - Akhmad Saehudin (Holistic al-Hadis, 2015)
One of the unique aspects in traditional Islamic scholarship is the using of isnâd system to report every saying from the author, particularly the prophetic hadîth. The so-strict attribution of isnâd to hadîth makes the sanad (p. asnâd; the chains of transmission) can not be detheched from the hadîth itself. Sanad is an element of hadîth in addition to râwî (collector) and matn (text of the hadîth). In further, sanad is regarded to as the source of the religion. This is because hadîth, from which Islamic doctrins are to be extracted, was transmitted by the authorities in the sanad. It is for this reason that the chains of transmission are of great attentions in the inqu ry of the authenticity of any hadîth. In exemining a hadîth from this aspect, as this article tries to elaborate, traditional Muslim specialists focused on three concerns: the continous connectivity of the chains of transmitter (itiṣâl al-sanad), the credibility of all transmitters (‘adâlah al-ruwât), and their intellectual capacity (ḍabṭ al-ruwât).